Factor analysis in a New-Keynesian model - Andreas Beyer; Roger E. A. Farmer; Jérôme Henry; Massimiliano Marcellino (European Central Bank (ECB), 2005)
New-Keynesian models are characterized by the presence of expectations as explanatory variables. To use these models for policy evaluation, the econometrician must estimate the parameters of expectation terms. Standard estimation methods have several drawbacks, including possible lack of identification of the parameters, misspecification of the model due to omitted variables or parameter instability, and the common use of inefficient estimation methods. Several authors have raised concerns over the validity of commonly used instruments to achieve identification. In this paper we analyze the practical relevance of these problems and we propose remedies to weak identification based on recent developments in factor analysis for information extraction from large data sets. Using these techniques, we evaluate the robustness of recent findings on the importance of forward looking components in the equations of the New-Keynesian model.
Keywords: E5; E52; E58; 330; determinacy of equilibrium; factor analysis; forward looking output equation; New-Keynesian Phillips Curve; Rational Expectations; Taylor rule; Faktorenanalyse; Neoklassische Synthese; Taylor-Regel; New-Keynesian Phillips Curve; Theorie